Interaction of Thromboplastin Apoprotein of Different Tissues with Concanavalin A - Evidence for Heterogeneous Glycosylation of the Human Apoprotein - van den Besselaar, A M H P; Bettina, R M (Thrombosis and Haemostasis, 1984)
Thromboplastin apoproteins of different tissues were solubilized with Triton X-100. Induction of plasma coagulation by these extracts was dependent on the presence of factor VII. Binding of the apoprotein-Triton complex to Concanavalin A- Sepharose 4B was studied. The apoprotein activity extracted from rabbit brain and bovine brain was almost completely bound to Concanavalin A-Sepharose. Under the same conditions, only partial binding was observed with human lung, human brain and human placenta apoprotein. These results suggest that human apoprotein is heterogeneous with respect to its carbohydrate moiety.
Keywords: Tissue thromboplastin; Concanavalin A; Glycosylation; Affinity chromatography